Indian clinical practice consensus guidelines for the management of laryngeal cancer - Singhal, Manish; Prabhash, Kumar; Babu, Govind; Chaturvedi, Pankaj; Kuriakose, Moni; Birur, Praveen; Anand, Anil; Kaushal, Ashish; Mahajan, Abhishek; Syiemlieh, Judita; Gairola, Munish; Ramachandra, Prakash; et al. (Indian journal of cancer, 2020)
Diagnosis Workflow for Evaluation of Clinical Stages Routine examination includes history and physical examination (with a complete head and neck exam, mirror and fiberoptic examination), a biopsy of primary site or fine-needle aspiration of the neck. Patients with arytenoid fixation, invasion of the posterior commissure, subglottic extension of more than 5 mm posteriorly and 5–10 mm anteriorly or to the upper border of the cricoid cartilage, cricoid cartilage invasion and major thyroid cartilage invasion (T4), massive pre-epiglottic space involvement, positive margins in a frozen section and extralaryngeal spread are not the candidates for organ preservation. For patients with glottic and supraglottic T4a, N0–3 larynx cancers, total laryngectomy with thyroidectomy ± unilateral/bilateral/contralateral neck dissection and paratracheal lymph node dissection, as indicated (depending on the node involvement) followed by adjuvant treatment (RT, or systemic therapy/RT may be considered), is recommended.